(untitled) (Brazilian Journal of Health Research, 2019)
Introduction: Congenital syphilis leads to miscarriage, fetal death and stillbirth. Vertical syphilis transmission can reach 50% to 85% in the primary stage of the disease among pregnant women. Prematurity, neurological sequelae, deafness, bone deformities may affect babies born from mothers who were not properly treated during prenatal care. Objective: Describing the incidence of congenital syphilis in Espírito Santo State from 2008 to 2011, as well as identifying factors influencing treatment failure. Methods: A descriptive cross-sectional study was developed based on secondary data collected in the Notifiable Diseases Information System and in the Live Birth Information System available at the IT Department of the Brazilian Unified Health System. Results: 857 pregnant women were diagnosed with syphilis and 538 cases of congenital syphilis were reported in Espírito Santo State from 2008 to 2011, which corresponded to 62.8% of cases. The number of pregnant women diagnosed with syphilis and the number of congenital syphilis cases increased during the analyzed period. Based on the numbers analyzed in the current study, 110 congenital syphilis cases and only 81 pregnant women diagnosed with syphilis were reported in 2009, which indicates the underreporting of these cases. Additional 107 cases of pregnant women diagnosed with syphilis were reported in 2010 in comparison to 2008, whereas 2011 reported 91 more cases than 2010. On the other hand, congenital syphilis recorded 57 more cases in 2011 than in 2008. The skin color of children diagnosed with congenital syphilis has shown concentration of cases: the disease affected more than 50% of brown children, who were followed by white (approximately 20%) and black children ( 15%). Although the infant mortality rate (regardless of causes) decreased in 2011, there was considerable increase in the number of deaths due to congenital syphilis. Conclusion: Socioeconomic and clinical factors are associated with high incidence of syphilis. Quality and affordable prenatal care play a key role in disease prevention. It is essential empowering and training health professionals to early identify and treat syphilis in women at reproductive age in order to prevent the disease from spreading.